Analisis Aspek Ketahanan Pangan Indonesia dengan Hard dan Soft Clustering, 2022 - Diarty, Milie; Wijayanto, Arie Wahyu (Universitas Trunojoyo Madura, 2024)
Food security is crucial all over the world. Even food security is one of the goals in the Sustainable Development Goals (SDGs). Indonesia has also made food security a goal in both short and long term development. As a country with geographical conditions that are coveted by other countries, it is only natural for Indonesia to be able to use existing resources to maximize domestic development, one of which is through food security. Provinces that are spread from Sabang to Merauke make Indonesia must be able to analyze the grouping of its food security by considering various indicators. Food security indicators are integrated into the aspects of food availability, affordability, and utilization. Clustering is a method in machine learning to be able to find out food security groupings in Indonesia. There are many clustering methods. Several methods that are widely used are Hierarchical, K-Means, and Fuzzy C-Means. All three can produce different groupings. In this study, it was found that there was one province that had low food security, namely Papua Province. In addition, some of the provinces that always have high food security are all provinces on the island of Java.